Development of Students' Professional Competence in Higher Professional Education (Journal of Pedagogical Inventions and Practices, 2022)
In the article today, the directions of Bachelor's degree in vocational education development of educational-cognitive motivations of students and improvement of their system of activation of effective educational processes through a new form of teaching, non-traditional techniques, taking into account that the development of professional competences of students in the field of vocational education is relevant today, the formation, the issues of acquisition of skills and skills and their application in practice at a high level, development of professional competence in them on the basis of an innovative approach to educational and cognitive activities have been interpreted